1987
DOI: 10.1016/0035-9203(87)90274-4
|View full text |Cite
|
Sign up to set email alerts
|

Endemic malaria in four villages of the Pakistani province of Punjab

Abstract: The prevalence of malaria in 4 villages 60 km south of Lahore, Punjab, where Anopheles culicifacies is the vector was estimated from blood films made during three mass malaria surveys (MS) and at 204 clinics (CS) held over 18 consecutive months. The highest parasite rate occurred during October 1984 when 43% of the CS population had parasitaemias. Plasmodium vivax predominated early in the major transmission season (23% and 15% vivax parasitaemias in August 1983 and 1984 respectively) whereas P. falciparum was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 5 publications
1
20
1
Order By: Relevance
“…P. vivax is more commonly distributed in temperate zones and is more prevalent than P. falciparum [21]. It is believed that P. vivax has the greater ability to produce gametocytemia under temperate conditions [22]. Furthermore, the possible explanation will be the climate change which might be responsible for the natural distribution of malaria [23,24] associated with P. vivax in this area.…”
Section: Resultsmentioning
confidence: 99%
“…P. vivax is more commonly distributed in temperate zones and is more prevalent than P. falciparum [21]. It is believed that P. vivax has the greater ability to produce gametocytemia under temperate conditions [22]. Furthermore, the possible explanation will be the climate change which might be responsible for the natural distribution of malaria [23,24] associated with P. vivax in this area.…”
Section: Resultsmentioning
confidence: 99%
“…Four villages having a high prevalence of both P. falciparum and P. vivax malaria were selected for cross-sectional and prospective study in the Kasur District of Punjab (Strickland et al, 1987). They are located on either side and within 20-200m of the Rohi drain, an irrigation drain with clear water and slow flow that supplies year-round breeding sites for anopheline mosquitoes, even during the dry season.…”
Section: Study Area and Populationmentioning
confidence: 99%
“…Previous studies have observed complex relationships among Plasmodium species in patients treated for syphilis, [2][3][4] and in surveys of naturally infected individuals living in malaria-endemic regions around the world. [5][6][7][8][9][10] Experimental infections involving nonendemic adults have shown that susceptibility to individual Plasmodium species may be influenced by the species of previous or current infections. [2][3][4] Natural infection relationships among human malaria species appear to vary based upon geographic differences, which are certain to involve not only bio-climatic variation but also genetic differences in human and vector populations.…”
mentioning
confidence: 99%
“…[2][3][4] Natural infection relationships among human malaria species appear to vary based upon geographic differences, which are certain to involve not only bio-climatic variation but also genetic differences in human and vector populations. [5][6][7][8][9][10] Microscopic examination of Giemsa-stained thick and thin blood smears has been the diagnostic method of choice for species identification in epidemiologic studies and medical diagnosis. 11 The major limitations of microscopy include lack of trained personnel and the length of time required for blood smear examination.…”
mentioning
confidence: 99%